2018
DOI: 10.18551/rjoas.2018-06.44
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Degree of Beef Cattle Market Concentration in Kupang of East Nusa Tenggara, Indonesia

Abstract: Beef cattle is a strategic commodity, economically, socially and culturally for the people of Nusa Tenggara Timur and Indonesia. This the study aims to measure the dynamics of the degree of market concentration of beef cattle sales in Kupang, Nusa Tenggara Timur for 2014-2017. The results show the dynamics of the concentration of beef cattle market is relatively moderate, shown by the consignment (CR4 and HHI) that fluctuate in 2014-2017. Fluctuating trends of market concentration indicates horizontal business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
1
4
1
Order By: Relevance
“…This result of the research was following previous research [24,38], arguing that the market concentration of beef cattle was classified as a higher concentration of oligopoly, so that it tends inefficient. In contrast, the result of this research was different from other previous researches, stating that the concentration level of the beef cattle market changed based on time, but the level was in low to a medium concentration where the oligopoly still enabled the entry of new actors in beef cattle market [39,26].…”
Section: Market Structurecontrasting
confidence: 99%
See 1 more Smart Citation
“…This result of the research was following previous research [24,38], arguing that the market concentration of beef cattle was classified as a higher concentration of oligopoly, so that it tends inefficient. In contrast, the result of this research was different from other previous researches, stating that the concentration level of the beef cattle market changed based on time, but the level was in low to a medium concentration where the oligopoly still enabled the entry of new actors in beef cattle market [39,26].…”
Section: Market Structurecontrasting
confidence: 99%
“…The level of ratio concentration, in addition, is 70-100 percent, the market structure of beef cattle is an oligopoly with a higher level of concentration, directing to monopoly market. While b), in Herfindahl index (HI), the analysis is to measure market strength [26]. HI is a sum of the market share square of all companies in the industry, by the following equation:…”
Section: Analysis Of the Market Structurementioning
confidence: 99%
“…This result is similar to a study conducted in Kupang -East Nusa Tenggara that analyzed the CR4 from the beef cattle market in 2014 -2017, which showed that the CR4 value is within 50.9% -70.8%. This indicated that the market concentration provides some benefits to the farmers or market players since it affects the prices (Roy, Ratya, Nuhfil & Wahib, 2018).…”
Section: Analysis Of Concentration Ratio In Input Intermediate and Output Marketsmentioning
confidence: 98%
“…The structure, conduct, and performance (SCP) approach can be used to analyze the inefficiency of the marketing system in terms of the causal relationship that is formed. Company conduct in the market is influenced by market structure and affects the performance of companies in the market (Nendissa et al, 2018). One of the proposed conceptual frameworks Azhara (2016), shows the market structure is formed by market supply and demand conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Asmarantaka et al (2017), also argues that there is a causality relationship between the variables SCP. Several studies of inefficient marketing system analysis using the SCP approach include Azhara (2016) related to milkfish market analysis, Abubakar (2016) examining Cocoa beans marketing channels, Roy (2018) related to cattle market analysis in East Nusa Tenggara. Their research analysis shows that inefficiencies in market performance consist of causality of market structure and influencing market behavior.…”
Section: Introductionmentioning
confidence: 99%